Sexual Life and Sexual Wellness in Individuals with Complete Androgen Insensitivity Syndrome (CAIS) and Mayer‐Rokitansky‐Küster‐Hauser Syndrome (MRKHS). (25th October 2013) - Fliegner, Maike; Krupp, Kerstin; Brunner, Franziska; Rall, Katharina; Brucker, Sara Y.; Briken, Peer; Richter‐Appelt, Hertha
Abstract Introduction Sexual wellness depends on a person's physical and psychological constitution. Complete Androgen Insensitivity Syndrome (CAIS) and Mayer‐Rokitansky‐Küster‐Hauser Syndrome (MRKHS) can compromise sexual well‐being. Aims To compare sexual well‐being in CAIS and MRKHS using multiple measures: To assess sexual problems and perceived distress. To gain insight into participants' feelings of inadequacy in social and sexual situations, level of self‐esteem and depression. To determine how these psychological factors relate to sexual (dys)function. To uncover what participants see as the source of their sexual problems. Methods Data were collected using a paper‐and‐pencil questionnaire. Eleven individuals with CAIS and 49 with MRKHS with/without neovagina treatment were included. Rates of sexual dysfunctions, overall sexual function, feelings of inadequacy in social and sexual situations, self‐esteem and depression scores were calculated. Categorizations were used to identify critical cases. Correlations between psychological variables and sexual function were computed. Sexually active subjects were compared with sexually not active participants. A qualitative content analysis was carried out to explore causes of sexual problems. Main Outcome Measures An extended list of sexual problems based on the Diagnostic and Statistical Manual of Mental Disorders, 4th ed., text revision, by the American Psychiatric Association and related distress. Female Sexual Function Index (FSFI), German Questionnaire on Feelings of Inadequacy in Social and Sexual Situations (FUSS social scale, FUSS sexual scale), Rosenberg Self‐Esteem Scale (RSE), Brief Symptom Inventory (BSI) subscale depression. Open question on alleged causes of sexual problems. Results The results point to a far‐reaching lack of sexual confidence and sexual satisfaction in CAIS. In MRKHS apprehension in sexual situations is a source of distress, but sexual problems seem to be more focused on issues of vaginal functioning. MRKHS women report being satisfied with their sex life. Conclusion Different conditions can affect individuals in diagnosis‐specific ways despite some shared clinical features. Professionals should adopt an interdisciplinary approach and provide custom‐made care in order to promote sexual well‐being in patients. Fliegner M, Krupp K, Brunner F, Rall K, Brucker SY, Briken P, and Richter‐Appelt H. Sexual life and sexual wellness in individuals with Complete Androgen Insensitivity Syndrome (CAIS) and Mayer‐Rokitansky‐Küster‐Hauser Syndrome (MRKHS). J Sex Med 2014;11:729–742.